HIV Treatment for Alcohol and Non-Injection Drug Users in El Salvador. (December 2015) - Dickson-Gomez, Julia; Bodnar, Gloria; Petroll, Andy; Johnson, Kali; Glasman, Laura
Since the mid-1990s, many developing countries have introduced and expanded the availability of combination antiretroviral therapy (cART) to persons living with HIV (PLH). However, AIDS-related mortality continues to be high particularly among drug users. In this article, we present results from in-depth interviews with 13 HIV medical providers and 29 crack cocaine and alcohol using PLH in El Salvador. Providers endorsed negative attitudes toward substance using PLH and warned PLH that combining cART with drugs and alcohol would damage their livers and kidneys resulting in death. Upon diagnosis, PLH received little information about HIV treatment and many suffered depression and escalated their drug use. PLH reported suspending cART when they drank or used drugs because of providers' warnings. Substance using PLH were given few strategies and resources to quit using drugs. Messages from medical providers discourage drug users from initiating or adhering to antiretroviral therapy (ART) and may contribute to treatment abandonment.